Persepsi Mahasiswa tentang Program Merdeka Belajar – Kampus Merdeka Pertukaran Pelajar - Nisrina Nurul Insani; Susan Fitriasari; Dede Iswandi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This article aims to observe students' perceptions of the MB-KM student exchange program, as well as what obstacles and barriers are experienced by students participating in the student exchange program. This research uses a case study method, with a focus on the implementation of an off-campus learning activity program, namely student exchange organized by the Citizenship Education study program, Universitas Pendidikan Indonesia. Observations were made on 23 Citizenship Education students in implementing a student exchange program at the Universitas Pendidikan Indonesia in Islamic law courses. Triangulation of data from observations, interviews, and field notes was used to analyze data collected during the implementation of student exchange activities. The findings of this study indicate that students have a favorable opinion of the Universitas Pendidikan Indonesia implementation of the student exchange program. The student exchange program is viewed as a means of developing an innovative learning culture through collaboration; however, the obstacles that activities frequently face are unexpected; there are issues with credit transfer, as well as student difficulties with adapting to a new environment and time management.